Organization Innovation Effect on Job Satisfaction and Employee Engagement Over Job Performance at PT. UTAC Manufacturing Services Indonesia - Hendra Lesmana; Rhian Indradewa; Tantri Yanuar R Syah (Journal of Multidisciplinary Academic, 2021)
This study aims to analyse the effect of organization innovation on job satisfaction also the influence effect of organization innovation and job satisfaction on job performance with the influence of employee engagement on job performance at PT. UTAC Manufacturing Services Indonesia. In this study, we use the employees’ population at PT. UTAC Manufacturing Services Indonesia. Here, the criteria of employee’s job such as operator, staff, and supervisor level. The sample data of observation was reached 300 employees who were considered to have represented as a population studied by using quantitative data methods (sampling technique). The results show the Organization Innovation had a positive and significant effect on Job Satisfaction. This result is implying that the better Organization Innovation carried out by PT. UTAC Manufacturing Services Indonesia, the better the Job Satisfaction. Furthermore, the Organization Innovation have a positive and significant effect on Employee Engagement. This means that the better Organization Innovation, the more increase employee engagement. Also, Employee Engagement also has positive and significant effect on Job Satisfaction, as well as a positive and significant influence of Job Satisfaction on Job Performance. This means that the better the Employee Engagement, the higher Job Satisfaction and the higher Employee Job Performance of PT. UTAC Manufacturing Services Indonesia, the Job Performance will increase.